Propafenone-Induced QRS Widening in a Child With Arrhythmogenic Right Ventricular Cardiomyopathy: A Case Report and Literatures Review - Chu, Yan-qiu; Wang, Ce; Li, Xue-mei; Wang, Hong (Frontiers in Pediatrics, 2020)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a rare cardiac disease in children, and can lead to sudden cardiac death (SCD). Propafenone is classⅠC antiarrhythmic medication, and its side effects include cardiovascular compromise in the form of hypotension, bradycardia, ventricular dysrhythmias, QRS widening and heart block. Propafenone has been reported causing QRS widening, but rarely in children. In this article, we presented a boy diagnosed with ARVC who meets diagnosis criteria based on typical symptoms, electrocardiograph (ECG), echocardiography (Echo), cardiac magnetic resonance imaging (CMRI), sudden death of first family member, and genetic mutation in desmosomal DSG2 gene. Antiarrhythmic drugs have been used for treating patients with ARVC, by eliminating or decreasing the occurring frequency of arrhythmias. As his ECG showed frequent premature ventricular contractions (PVC), he was prescribed with oral propafenone. One day after the drug treatment, he presented dizziness accompanied with significant QRS widening in ECG. His dizziness was improved when Propafenone dose was reduced, and resolved after sotalol replacement, with ECG recovered to nearly normal state of QRS. Propafenone may lead to QRS widening and increase the risk of ventricular tachycardia, and it may not reduce ARVC associated mortality. This report may serve as a precaution for clinicians when providing cares for ARVC patients.